Ancient life on Mars??? - Treiman, Allan H.; Dasch, Pat; orcid:0000-0002-8073-2839 (Lunar and Planetary Institute, 1997)
LPI slide set converted to a PowerPoint set by the staff of the Spacecraft Planetary Imaging Facility, Cornell University Photographs and drawings of Mars, meteorites, Antarctica, bacteria and future missions to Mars, examining the possibility of Martian life in general and ALH 84001. compiled by Pat Dasch and Allan Treiman Mars -- Mars: Ancient Highlands -- Mars: Young Volcanic Terrain -- Mars Lake Sediments -- Mars: Drainage Channels -- Water Channels on Earth -- Mars "Splosh" Crater -- Mars "Ray" Crater -- The Surface of Mars -- Meteorite with Fusion Crust -- Lunar Meteorite ALHA 81005 -- Martian Meteorite EETA 79001 -- ANSMET Antarctic Meteorite Collection Sites -- Blue Ice in Antarctica -- ANSMET Field Camp -- ANSMET Collecting a Meteorite -- Processing a Meteorite -- ALH 84001 -- The History of ALH 84001 and of Life on Earth -- The Origin of Life on Earth -- ALH 84001 in Thin Section -- ALH 84001 Carbonate Globules -- Carbonate Minerals in the Ivuna Meteorite -- Magnetite Grains in ALH 84001 Carbonate -- Polycyclic Aromatic Hydrocarbons -- ALH 84001: Bacteria Shapes -- Earth Bacteria -- E. coli -- ALH 84001 Possible Fossil Object -- Nanobacteria on Earth? -- Extreme Environment: Black Smoker--Ancient Life: Apex Chert Microfossils -- Interplanetary Dust Particles -- Possible Source for Martian Meteorite ALH 84001 -- Mars Global Surveyor -- Mars Pathfinder -- Mars Pathfinder Landing Site -- Mars Surveyor '98 Lander -- Mars Sample Return -- 2020 Vision: Exobiology Survey of Dao Vallis -- Beta Pictoris.